Surveying preschool teachers’ use of digital tablets: general and technology education related findings - Otterborn, Anna; Schönborn, Konrad; Hultén, Magnus (International journal of technology and design education, 2019)
The availability of digital tablets in preschools has increased significantly in recent years. Literature suggests that these tools can enhance students’ literacy and collaborative skills. As society becomes increasingly digitized, preschool curriculum reform also emphasises the subjects of technology and science as priority areas of learning. Teachers’ knowledge and experiences are of utmost importance in carrying out this mandate. Few studies have explored the use of digital tablets to teach preschool technology and science in Sweden, and there is an urgent need to ascertain the role of digital aids as teaching tools. This survey study seeks to determine how digital tablets are used to support preschool children’s learning in general, and with respect to technology education. Preschool educators (n = 327) across Sweden responded to an online survey consisting of 20 closed and 6 open items that probed the use of digital tablets. Survey results revealed a high degree of engagement with digital tablets in preschools, with activities directed toward various subject-related, social and generic skills. Programming, invention, construction and creation, problem-solving, and design emerged saliently as tablet activities in technology subject areas. Opportunities for providing meaningful learning tasks and digital adaptability were seen as pedagogical benefits of using tablets, but increasing expectations to integrate tablet activities with an accompanying lack of digital skills were expressed as limitations. Teachers’ recommendations for future tablet use included defining clearer curriculum guidelines for tablet implementation and adequate training for acquiring digital competence.